The Religious Fraternities and Brotherhoods of Seville: Servant Leadership in Social Action - Barrera Blanco, Gonzalo; Martín Ríos, Blanca; Senent-De Frutos, Juan Antonio (Frontiers in Psychology, 2020)
The religious fraternities and brotherhoods of Seville, Spain, are among the major agents of the social aid carried out in that city. Knowing the characteristics of the service leadership that have been established by authors such as Greenleaf (1997), we interviewed several representatives of these institutions to determine if they would meet those characteristics and to what extent they configure their teams in charge of carrying out that social aid. Our aim was to verify, through the Rivera and Santos questionnaire (2015), which has been modified to refer to a legal person, if the characteristics that have been assigned to the concept of leader-server and that normally apply to a natural person can also be identified in such corporations. Moreover, we sought to take the opportunity to investigate this structure of work in social action and identify the common characteristics, if any, that make the fraternities and brotherhoods of Seville different from other private agents fighting against poverty.